Drug-related problems (DRPs) in geriatric patients with type 2 diabetes mellitus (T2DM): a review - Lathifa Nabila; Sundas Ejaz; Shalahuddin Al Madury (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2022)
Asthma is an inflammatory airway disease characterized by bronchial hyper-responsiveness, reversible airflow limitation, and respiratory symptoms. Asthma affects 300 million people in developed countries. More than 10% of asthma complaints in children occur at school age. Asthma therapy in children using pharmacological agents is still the main choice until now. However, the response of pediatric patients to asthma treatment varies. In addition to age, organ function, and drug interactions, genetic factors are often associated with drug response variability. This variability can occur due to single nucleotide polymorphisms (SNP) in protein-coding genes that play a role in bioavailability and drug response. Understanding of pharmacogenomics as the basis of individualized medicine aims to avoid adverse drug reactions and maximize drug effectiveness. The existence of genetic variation allows the drug response between individuals to be different. Pharmacogenomics provides important information in individual-based medicine so that it can predict the existence of a population that can respond well to certain drugs and a population that has a higher risk of adverse drug reactions. Implementation of individual treatment can optimize treatment in patients because the dose of treatment and therapeutic options have been adjusted based on individual genetic characteristics.